KENAL DIRI SECARA QUR’ANI MELALUI PROSES TERCIPTANNYA MANUSIA SEBAGAI MODAL PENGUATAN KARAKTER - Khususiyah, Khususiyah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2018)
Knowing the Qur'anic self through the process of human creation is a very simple and fundamental way of reinforcing individual character. Thus, the key concept in writing this article is to know yourself in the Qur'an. With the hope of knowing themselves in the Qur'an will understand each in-dividu in order to be able to portray and position themselves well and correctly (character). As it is written in the Holy Qur'an (Surat 51: 21) which means, "And (also) to yourself. Then do you not pay attention? "From the verse clearly explained that self-know is an important thing that must be done by every individual. Know yourself in this discussion is an attempt to understand the potential - potentially very potential in individuals based on / through the process of creating human beings as an individual character enhancer in order to make efforts to avoid the mall of continuous practice / prolonged in empowering the potential self-that is able to undermine the strengthening of individual characters themselves. In the sense of self-knowledge, each individual will be able to empower the potentials that exist within him with honest, intelligent, tough and caring. It is a package in one complete sequence to assure the strengthening of individual characters. Potential - the potential of such potential, is not always able to strengthen the character if not understand the first type and how to memperdayakannya (self potential) can even fall on the contrary that is actually exaggerate the character. As the Word of ALLOH S.W.T in (QS 91: 7-10). Therefore, we must be able to determine the right pattern or method or way of reading so that this process of understanding can produce a characteristic personality. One of the methods to be used in this article is the Bismi Robbik method (QS.96: 1) which will help us in the process of knowing ourselves completely and correctly. In this article, the authors attempt to expose globally though with all the limitations of ability in terms of efforts to understand the process of creation of the human Qur'an as capital strengthening character.